G188(P) Understanding the experiences of people living with sickle cell disease- a UK-wide study. (27th April 2016) - Chakravorty, S; Tallett, A; Witwicki, C; Mkandawire, C; Ogundipe, A; Ojeer, P; Whittaker, AJ; Thompson, J; Sathyamoorthy, G; Warner, JO
Abstract : Aims: Sickle cell disease (SCD) is a chronic multisystem disorder resulting in debility, organ damage, frequent hospitalisations and reduction in lifespan; affecting over 10, 000 people in the UK. Since the care experience of people living with SCD in the UK is not known, this research aimed to develop a series of tools to facilitate this understanding. Methods: We undertook focus group discussions to identify areas of concern in care experience in people living with SCD. This informed the development of three Patient Reported Experience Measure questionnaires, with 33–38 questions each, aimed at (a) children aged 8–15, (b) parents and carers of children with SCD and (c) adults with SCD. A fully cognitively tested pilot questionnaire survey was instituted to validate the questionnaires and gather patient and carer perspectives. Between March and October 2015 we undertook fieldwork to obtain responses from each survey group, with an aim to obtain at least 200 responses from each group. Results: Key areas highlighted at the initial focus group discussions were: access to good quality primary care, A&E and psychology services; transition from paediatric to adult services and concerns regarding the physical, psychological, social and financial impact of the condition. We received a total of 736 questionnaire responses, with >200 responses from each group indicated above, with most responses from adolescents with SCD (or their parents) see Figure 1 . Preliminary analysis indicated a widespread prevalence of negative thoughts and feelings when living with SCD, as indicated by >500 free text responses informing the word cloud in Figure 2 . Only a third of all respondents received adequate information about treatment options and two-thirds indicated that staff in emergency departments were not fully knowledgeable in SCD. Staff delivering planned hospital care knew more about SCD than those delivering unplanned hospital care or primary care, see Figure 3 . The survey validation demonstrated that the surveys functioned well and contributed to the measurement of patient experience, with little evidence of non-response and drop-out. Conclusion: This is the first and the largest survey of care experience of SCD in the UK and will inform future delivery, design and commissioning of services for people with SCD.